ОСНОВНЫЕ ПСИХОТЕРАПЕВТИЧЕСКИЕ ПОДХОДЫ ПРИ РЕАКЦИЯХ УТРАТЫ («Наука и здравоохранение», 2026)
In this article gives the basic psychotherapeutic tactics at reactions of loss, described four tasks of sorrow, it’s forms andmethods of decision, presented role of psychotherapeutics at reactions of loss, described universal steps, for recovery tonormal life.